(untitled) (Scientific journal of the Fergana State University, 2023)
The article examines the concept of "beauty", its eastern and western interpretations. In the representation of beauty through the symbol of a woman, various and general aspects of beauty standards in the East and in the West are analyzed. The verbalization of the criteria of aesthetic assessment in the language is considered.